Correlation Between Corneal Curvature/Axial Length Ratio and Refractive Error. - Chakraborty, Shoubhik; Yadav, Pradeep; Mallick, Mantu (Optometry & Visual Performance, 2025)
Purpose: Ocular biometric parameters significantly influence the refractive status of the eye, particularly axial length and corneal curvature. These parameters play a crucial role in determining an individual's refractive error, making them vital components in understanding vision health. Emmetropization is the physiological process through which the axial length of the eyeball and corneal curvature adjust to maintain an emmetropic (normal) state of vision. This complex interplay is essential for ensuring that light entering the eye is properly focused on the retina. Methods: This study conducted a retrospective analysis to investigate the relationships between refractive error and biometric parameters in a cohort of males 25 years of age (n=125). The principal biometric parameters examined in this study included average corneal curvature and axial length, measured using the Zeiss IOL Master 700. These parameters are critical for understanding the structural aspects of the eye that influence refractive errors. The ratio between axial length and corneal curvature was calculated for correlation. Results: Spearman correlation revealed that axial length and the average corneal curvature showed the strongest correlation: -0.849. This indicates that in cases of high hypermetropia, the AL/CR ratio tends to be lower, whereas in high myopia, the ratio increases. Conclusions: The axial length (AL) to corneal radius of curvature (CR) ratio is a critical biometric parameter, particularly when assessing refractive errors. This ratio tends to be highest in myopic patients, where an elongated axial length combined with a flatter cornea leads to increased myopia. Conversely, hypermetropic (farsighted) patients exhibit a lower AL/CR ratio, characterized by a shorter axial length and steeper cornea.